Financial study and the relationship between farmer identity and the income of lowland rice farmers in Selubuk Village, Air Napal District, North Bengkulu Regency - Sarina; Hasibuan, Ikhsan; Asfaruddin; Suzanna, Eka (Fakultas Pertanian Universitas Yudharta Pasuruan, 2025)
Introduction: This study aims to analyze the financial feasibility and identify the influence of total production, planting area, and farmer identity (age, education level, farming experience, number of family dependents) on the income of lowland rice farmers in Selubuk Village, Air Napal District, North Bengkulu Regency. Methods: This study used a quantitative approach with a survey method on 29 farmer respondents selected from 97 farmer families using the Slovin formula. Primary data were collected through questionnaires and interviews, while secondary data were obtained from related agencies. Data analysis included cost-revenue analysis (R/C ratio) and multiple linear regression analysis. Results: The results showed that lowland rice farming in Selubuk Village was financially feasible with an R/C ratio value of 3.39. The regression analysis results indicated that simultaneously, total production, planting area, age, farming experience, education level, and number of family dependents had a significant effect on farmer income (Sig. F = 0.000). Partially, the variables of total production, planting area, farming experience, and education level had a positive and significant effect on farmer income (p < 0.05). However, a multicollinearity problem was detected between the total production and planting area variables, which needs attention in the interpretation of their individual coefficients. The variables of age and number of family dependents did not have a significant effect on farmer income (p > 0.05). Conclusion: In conclusion, lowland rice farming in Selubuk Village is profitable, and income improvement can be focused on production factors, experience, and increasing farmer education capacity, considering the close relationship between production and land area.